Effects of a Formula-Based Ketogenic Diet on Refractory Epilepsy in 1 to 3 Year-Old Patientsunder Classic Ketogenic Diet - Karimzadeh, Parvaneh; Moosavian, Toktam; Moosavian, Hamid Reza (Iranian Journal of Child Neurology, 2019)
Abstract Objectives: The classic ketogenic diet (CKD) as a potential epilepsy treatment with high-fat has not a good tolerability in some patients, and so many families refuse to use this diet for long term especially in children younger than 2 years of age. In the present study, the efficacy and tolerability of the only CKD was compared with CKD combined a formula-based powder in children between 1 and 3 years of age with intractable epilepsy. Material and Methods: We prospectively enrolled 45 children with refractory epilepsy for CKD (control group), and CKD combined with a formula-based powder (experimental group) treatment. Subjects were followed up for at least six months. Results: Most of the patients in control group did not tolerate the diet and were reluctant to eat homemade foods with high fat, as all the families of the patients younger than 2 years old in this group chose to discontinue the CKD and pursued other options. 33% of the families of patients younger than 2 years old and totally 41.6% patients between 1-3 years old in experimental group stayed to the end of the trial, and all of them showed more than 90% reduction in seizure frequency after 6 months. Also, regardless of the other variables, the formula increased the chance of responding to treatment 7.32 times. Conclusions: A ketogenic diet using a formula-based powder is effective, safe, and tolerable in infants and children with refractory seizure especially for younger patients who are reluctant to eat homemade foods.